ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERINVESTASI DI PASAR MODAL BAGI GENERASI MILENIAL - Shinta Wahyu Hati; Windy Septiani Harefa (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
The purpose of this research was to determine motivation, capital market knowledge, and preferences for interests. This type of research is explanatory research with quantitative research. The research population is students majoring in business management who have participated in capital market and financial management courses. The sampling technique using purposive sampling, data collection using a questionnaire. The sample of this research were students in the Department of Business Management who received 67 Business Finance or Capital Market courses. The results of this study indicate that there is no motivation for millennial generation investment interests, there is a relationship with capital market knowledge of millennial generation investment interests, is a preferential preference for millennial generation investment interests. There are simultaneous influences on motivational variables, capital market knowledge, and risk preferences for investment interest in millennial generation